Living history - Clinton, Hillary Rodham (New York : Scribner, 2003)
[The author writes] about her upbringing in suburban, middle-class America in the 1950s and her transformation from Goldwater Girl to student activist to controversial First Lady. [This book] is her revealing memoir of life through the White House years. It is also her chronicle of living history with Bill Clinton. -Dust jacket.
Keywords: Clinton, Hillary Rodham -- Non-fiction; Clinton, Bill, 1946 -- Non-fiction